2022
DOI: 10.1186/s12871-022-01878-0
|View full text |Cite
|
Sign up to set email alerts
|

The combination of lactate level, lactate clearance and APACHE II score better predicts short-term outcomes in critically Ill patients: a retrospective cohort study

Abstract: Background The mortality rate is high in critically ill patients due to the difficulty of diagnosis and treatment. Thus, it is very important to explore the predictive value of different indicators related to prognosis in critically ill patients. Methods This was a retrospective cohort study of patients in the intensive care unit (ICU) of the Sixth People’s Hospital in Shanghai, China. A total of 1465 ICU patients had lactate values > 2.1 mmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Furthermore, a correlation was established between decreasing LC and increasing mortality. [5]. Our study revealed that high-risk patients who died, received MV or VS, and were admitted to the ICU had lower levels of LC compared to mild-moderate risk patients.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Furthermore, a correlation was established between decreasing LC and increasing mortality. [5]. Our study revealed that high-risk patients who died, received MV or VS, and were admitted to the ICU had lower levels of LC compared to mild-moderate risk patients.…”
Section: Discussionmentioning
confidence: 58%
“…The primary factors contributing to excessive lactate production include hypoxia, alterations in mitochondrial oxidation, and glycolysis [13]. There are many studies in the literature about the prognostic power of lactate in critically ill geriatric patients, hemorrhagic shock, and trauma, where there is tissue hypoperfusion [5,14,15,16]. ED often employs serum lactate levels to assess several acute medical conditions [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations